A technique of minimally invasive aortic valve replacement: an alternative to transcatheter aortic valve replacement (TAVR) - Henderson, Luke B.; Song, Zuorui; Sun, Xiaotian; Pirris, John P. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Minimally invasive aortic valve replacement (AVR) is increasingly being adopted worldwide, in which a right mini-thoracotomy (RT) approach plays an important role. Here we reported a novel technique of AVR via RT using sutureless prosthesis, without rib division or groin incision. Surgical access was performed through an anterior right thoracotomy with 5-cm skin incision placed in the third intercostal space. Percutaneous femoral-femoral cardio-pulmonary bypass (CPB) was applied under fluoroscopy guidance to avoid groin incision. A 5-mm stab incision was made in the right chest wall for aortic cross-clamping. A sutureless bioprosthetic valve was utilized in the limited operative field, which reduced the cross-clamp and CPB time. The patient was discharged on post-operative day 2, without obvious cross-valvar gradient, and with no pain or other complication. This report offers a more minimally invasive approach to AVR with proven durable valves, which can benefit high-risk patients.